P18.11.A Active beam scanning proton therapy for large skull base benign meningiomas: long-term results. (5th September 2022) - Amelio, D; Lo Faro, L; Corsini, F; Donner, D; Chioffi, F; Volpin, F; Volpin, L; Chierichetti, F; Sarubbo, S; Scartoni, D
Abstract: Purpose: To report long-term results of active beam scanning proton therapy (PT) for large skull base benign meningiomas Material and Methods: Eighty-two patients (pts) with large skull base meningiomas were treated with PT between April 2015 and December 2021. Median age was 62 years (range, 48-82) while KPS ranged between 60 and 100 (median 90); 60 were female (73%), and 22 were male (27%). Thirty-two pts (39%) had histologically proven World Health Organization (WHO) Grade I tumors. In remaining pts diagnosis was based on the typical imaging appearance of benign meningioma. All patients received PT for residual, progressive or non-operable lesions. Newly diagnosed tumors received total dose of 50 GyRBE (RBE: relative biologic effectiveness) while progressing meningiomas 54 GyRBE. All the treatments were delivered at 2 GyRBE per fraction. All pts were treated with active beam scanning PT using 3 fields with single field optimization technique. Treatment planning was based on morphological magnetic resonance imaging (MRI) with contrast enhancement medium administration. All pts received also 68-Ga-DOTATOC-PET. Gross tumor volume ranged from 21 to 64 cc. Toxicity was assessed according to Common Terminology Criteria for Adverse Events version 4.0. Median follow-up time was 40 months (range, 3-83). Results: All pts completed the treatment without breaks. Registered acute side effects include grade 1 (19%) and grade 2 (8%) skin erythema, grade 1 (5%) and grade 2 (5%) alopecia, grade 1 (40%) fatigue, grade 1 (5%) and grade 2 (10%) conjunctivitis, grade 1 (10%) pain, grade 1 (5%) blurred vision, grade 1 (10%) headache, and grade 2 (5%) skin hyperpigmentation. One pts (1%) experienced grade 3 pain. There were no further grade 3 or higher acute toxicities. Registered late side effects include grade 1 (2%) and grade 2 (5%) alopecia, grade 1 (21%) fatigue, grade 1 (5%) and grade 2 (5%) headache, grade 1 (6%) dizziness, grade 1 (3%) blurred vision, grade 1 (3%) and grade 2 (6%) pain, grade 1 (2%) dry eye, and grade 1 (5%) skin hyperpigmentation. Two pts (2%) experienced grade 3 pain. Two further pts (2%) experienced grade 3 optic neuropathy. There were no further grade 3 or higher late toxicities. During follow-up one pts (1%) with cavernous sinus meningioma experienced complete obstruction of intracavernous carotid artery with mild transient symptoms that resolved in few days and brain tissue ischemia detected at MRI (grade 2). Before irradiation this pts already had a meningioma-related near-complete obstruction of the intracavernous carotid artery and received a vascular surgery evaluation. Currently, absolute tumor control is 99%. Moreover, relief of symptoms recorded before irradiation occurred in 40% of pts. Conclusion: PT is safe and effective treatment for pts with large skull base benign meningiomas.